Justification of military neutrality of the Republic of Serbia at a time of erosion of neutrality in Europe - Kajtez Ilija; Starčević Srđan (Srpska Politička Misao)
This paper aims to examine the justifiableness of the Republic of Serbia's politics of military neutrality after the beginning of the Russo-Ukrainian conflict, i.e., in an era of extreme tensions between Western countries and Russia. The significance of this topic has been additionally elevated after two neutral countries, Sweden and Finland, renounced neutrality while debates about the appropriateness of neutrality emerged in other neutral countries, such are Ireland, Malta, and Austria. The purpose of the paper is to examine, from a perspective of sociology of politics, whether the position of military neutrality still represents a good foreign-policy strategy aiming to preserve sovereignty and territorial integrity. The hypothesis of this paper is that Serbia's military neutrality is justified by the social reality in Serbia. The first chapter briefly describes the historical decline of neutrality during the first half of the 20th century. In that context, observation made in mid last century, according to which neutrality was becoming an obsolete concept, is true. Increase of NATO members, as well as abandoning neutrality under the influence of globalization and negative experiences of neutral countries in the 20th century, strengthens this assertion. However, we can conclude that neutrality has existed in continuity in Europe throughout the entire modern period of history, and that there were always some states that chose neutrality, with larger or lesser prospects of success in realization of their security interests. The great revolution, one might say the collapse of neutrality or even a frenzy to align, was the result of the Russo-Ukrainian conflict and new increasing tensions between the West and Russia. The second chapter is dedicated to the causes of Serbia's decision to be military neutral. These causes include: internal division of key political acters in regards to strategic alignment, the issues of the status of Kosovo and Metohija in which the Russian Federation provides key support to Republic of Serbia in the United Nations, and the role of NATO in wars during the disintegration of Yugoslavia and currently in Kosovo and Metohija. The third chapter lists the advantages in regards to social values implied by the position of military neutrality. Authors conclude that military neutrality represents a favorable strategic option for the Republic of Serbia, not just due to painful collective memory of Serbian citizens of the NATO aggression on Yugoslavia and the support of the Russian Federation to Serbia in regards to Kosovo and Metohija, but also due to the intrinsic values of neutrality which could become an identity attribute and a foundation of the renewal of solidarity in Serbian society.